1999
DOI: 10.1056/nejm199912163412501
|View full text |Cite
|
Sign up to set email alerts
|

Efavirenz plus Zidovudine and Lamivudine, Efavirenz plus Indinavir, and Indinavir plus Zidovudine and Lamivudine in the Treatment of HIV-1 Infection in Adults

Abstract: As antiretroviral therapy in HIV-1-infected adults, the combination of efavirenz, zidovudine, and lamivudine has greater antiviral activity and is better tolerated than the combination of indinavir, zidovudine, and lamivudine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

35
528
4
20

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 927 publications
(587 citation statements)
references
References 40 publications
35
528
4
20
Order By: Relevance
“…1,7,[9][10][11][12][13][14] Gastrointestinal (GI)-related side effects such as nausea, vomiting, and diarrhea have been among the most commonly reported medication toxicities leading to regimen discontinuation in numerous studies. 1,7,12,13,15,16 Other studies have shown that certain patient characteristics such as race, gender, or socioeconomic status may predict higher rates of regimen discontinuation.…”
Section: Introductionmentioning
confidence: 99%
“…1,7,[9][10][11][12][13][14] Gastrointestinal (GI)-related side effects such as nausea, vomiting, and diarrhea have been among the most commonly reported medication toxicities leading to regimen discontinuation in numerous studies. 1,7,12,13,15,16 Other studies have shown that certain patient characteristics such as race, gender, or socioeconomic status may predict higher rates of regimen discontinuation.…”
Section: Introductionmentioning
confidence: 99%
“…7 Furthermore, persistent viral replication (plasma HIV RNA >500 copies/mL) has been reported under HAART in 10-40% of anti-viral therapy-naive individuals as a result of transmission of drug-resistant HIV-1 variants. 8 The management and effective treatment options for HIV/ AIDS clearly depend upon the development of PIs and other novel anti-HIV therapeutics, which can effectively combat drug-resistant HIV strains, possess better pharmacokinetic properties, have no or less toxicities, and come at reduced costs of synthesis.…”
mentioning
confidence: 99%
“…2,3,5,[10][11][12] More recently, based on studies showing greater effectiveness and tolerability, HIV-infected patients are increasingly prescribed antiretroviral regimens, which include HIV-1-specific non-nucleoside analog reverse transcriptase inhibitors (NNRTIs), such as nevirapine (NVP) and efavirenz (EFV), instead of PIs. [13][14][15][16][17] In addition, the emergence of HIV-1 drug resistance among antiretroviral-experienced patients has led to the more frequent use of HAART, which includes both PIs and NNRTIs. 17 However, nevirapine use has been associated with significant hepatic injury, severe cutaneous hypersensitivity reactions (with or without hepatitis) and, rarely, death.…”
mentioning
confidence: 99%
“…Accordingly, the United States Food and Drug Administration has issued warnings regarding the risk of NVP-related hepatotoxicity. 5,15,[18][19][20][21][22][23][24][25][26][27][28] Conversely, although reported, little published information is available regarding the risk of hepatotoxicity among patients receiving efavirenz. [29][30][31] Furthermore, most data regarding NNRTI-associated hepatotoxicity are derived from anecdotal reports, which may focus attention on exceptional cases or high-risk populations, or from clinical trials, which are frequently restricted to persons at low risk for adverse events.…”
mentioning
confidence: 99%